2017
DOI: 10.1371/journal.pmed.1002403
|View full text |Cite
|
Sign up to set email alerts
|

Associations between an IgG3 polymorphism in the binding domain for FcRn, transplacental transfer of malaria-specific IgG3, and protection against Plasmodium falciparum malaria during infancy: A birth cohort study in Benin

Abstract: BackgroundTransplacental transfer of maternal immunoglobulin G (IgG) to the fetus helps to protect against malaria and other infections in infancy. Recent studies have emphasized the important role of malaria-specific IgG3 in malaria immunity, and its transfer may reduce the risk of malaria in infancy. Human IgGs are actively transferred across the placenta by binding the neonatal Fc receptor (FcRn) expressed within the endosomes of the syncytiotrophoblastic membrane. Histidine at position 435 (H435) provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…Finally, a recent study from Benin found that PM was associated with decreased cord‐to‐maternal ratios of most blood stage‐specific antibodies. In the same study, a specific maternal IgG3 polymorphism (histidine at position 453) was associated with enhanced transplacental transfer of malaria‐specific IgG3, and offspring of women with this mutation had a reduced risk of malaria in infancy . Together, these studies suggest that PM, along with additional maternal factors, may affect the transfer of malaria‐specific antibodies, but the consequences of this in the offspring remain unclear.…”
Section: Maternal Malaria and Transplacental Antibody Transfermentioning
confidence: 91%
See 1 more Smart Citation
“…Finally, a recent study from Benin found that PM was associated with decreased cord‐to‐maternal ratios of most blood stage‐specific antibodies. In the same study, a specific maternal IgG3 polymorphism (histidine at position 453) was associated with enhanced transplacental transfer of malaria‐specific IgG3, and offspring of women with this mutation had a reduced risk of malaria in infancy . Together, these studies suggest that PM, along with additional maternal factors, may affect the transfer of malaria‐specific antibodies, but the consequences of this in the offspring remain unclear.…”
Section: Maternal Malaria and Transplacental Antibody Transfermentioning
confidence: 91%
“…IgG1 is preferentially transferred, followed by IgG4, IgG3 and finally IgG2, the cord level of which is often lower than the maternal level . Factors that are known to affect the transport of IgG include maternal hypergammaglobulinaemia, (which is hypothesized to result from FcRn saturation), maternal HIV and alterations in the binding domain of IgG to FcRn . Maternal malaria, in particular PM, is associated with elevated total maternal IgG as well as placental pathology, both of which might affect the transfer of maternal antibodies .…”
Section: Maternal Malaria and Transplacental Antibody Transfermentioning
confidence: 99%
“…There are likely several reasons for this notable absence, including concerns about half-life, proteolytic susceptibility of the hinge and allotypic polymorphisms [46][47][48][49]. Chief among these perhaps, the majority of IgG3 allotypes bear an Fc sequence in which a histidine residue key to pH-dependent binding to the neonatal Fc receptor (FcRn) responsible for antibody recycling and the long half-life of IgGs [50,51] is substituted with an arginine. Thus, in early studies, rapid plasma clearance was presumed to be a global attribute of IgG3.…”
Section: Introductionmentioning
confidence: 99%
“…The geometric mean of parasitemia was 8,702 parasites/μL (confidence interval [CI] = 7,163-10,570) in Group A, whereas in Group B it was 8,955 parasites/μL (CI = 6,973-11,501). The median weight of study participants was 11 kg (IQR = 8-16) and 23 kg (IQR = [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] in Group A and B, respectively ( Table 2). All differences were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…14 Several studies have associated its allelic variability with geographical location and the intensity of malaria transmission. [15][16][17] Genetic variation has been shown to contribute to reduced acquired immunity in P. falciparum as immunity is essentially strain-specific (Gandhi et al, 2014;Ocholla et al, 2014;Dechavanne et al, 2017). [18][19][20] Information on the allelic heterogeneity of the R2 region of the GLURP gene over a period of time will be valuable for research and development of antimalarial vaccines.…”
Section: Introductionmentioning
confidence: 99%